Lettuce‐produced hepatitis C virus E1E2 heterodimer triggers immune responses in mice and antibody production after oral vaccination. Issue 12 (9th June 2017) - Clarke, Jihong Liu; Paruch, Lisa; Dobrica, Mihaela‐Olivia; Caras, Iuliana; Tucureanu, Catalin; Onu, Adrian; Ciulean, Sonya; Stavaru, Crina; Eerde, Andre; Wang, Yanliang; Steen, Hege; Haugslien, Sissel; et al.
Summary: The hepatitis C virus (HCV) is a major etiologic agent for severe liver diseases ( e.g . cirrhosis, fibrosis and hepatocellular carcinoma). Approximately 140 million people have chronic HCV infections and about 500 000 die yearly from HCV‐related liver pathologies. To date, there is no licensed vaccine available to prevent HCV infection and production of a HCV vaccine remains a major challenge. Here, we report the successful production of the HCV E1E2 heterodimer, an important vaccine candidate, in an edible crop (lettuce, Lactuca s ativa ) using Agrobacterium ‐mediated transient expression technology. The wild‐type dimer (E1E2) and a variant without an N‐glycosylation site in the E2 polypeptide (E1E2∆N6) were expressed, and appropriate N‐glycosylation pattern and functionality of the E1E2 dimers were demonstrated. The humoral immune response induced by the HCV proteins was investigated in mice following oral administration of lettuce antigens with or without previous intramuscular prime with the mammalian HEK293T cell‐expressed HCV dimer. Immunization by oral feeding only resulted in development of weak serum levels of anti‐HCV IgM for both antigens; however, the E1E2∆N6 proteins produced higher amounts of secretory IgA, suggesting improved immunogenic properties of the N‐glycosylation mutant. The mice group receiving the intramuscular injection followed by two oral boosts with the lettuce E1E2 dimer developed a systemic but also a mucosal immune response, as demonstrated by the presence of anti‐HCV secretory IgA in faeces extracts. In summary, our study demonstrates the feasibility of producing complex viral antigens in lettuce, using plant transient expression technology, with great potential for future low‐cost oral vaccine development.